Utilización de la hoja de agave americana (cabuya) para el engorde de conejos de la raza neozelandes en el Centro de Estudios Academicos Salache (CEASA) - Carvajal Jacome, Claudia Liset (2014)
This research study has made in the neighborhood Salache - Bass, Salache Parish, Canton Latacunga belonging the province of Cotopaxi, Ecuador. It has a general explanation of the management , breeding, production , life cycle and population of rabbits existing in our country, state, and university focused exclusively on New Zealand race found in higher percentage , the implementation of new diets is also supported with other type of plants and fodders , in this case the Americans Agave ( sisal ) was presented as overfeeding for the nutrition of rabbits from which excellent benefits are gotten for its high quality and quantity of nutrients such as protein, fiber , amino acids , vitamins and minerals....